PEMBUATAN ELEKTRODA KARBON AKTIF DARI TANDAN KOSONG BUAH AREN DENGAN VARIASI SUHU KARBONISASI - Irma Apriyani; Rakhmawati Farma (Komunikasi Fisika Indonesia, 2021)
The preparation and characterization of the physical properties of activated carbon electrodes derived from the biomass of empty palm fruit bunches were analyzed by varying the carbonization temperature. Biomass of empty palm fruit bunches is selected as a base material for making carbon electrodes throught a pre-carbonization process, chemical activation with KOH 0.5 M activator, carbonization process with variations in temperature 650 °C, 700 °C, 750 °C, and 800 °C under an N2 gas environment, and activated by CO2 gas at 900 °C. Reduce of carbon mass by 20.182 % and produce carbon powder. Thermogravimetry show that thermal resistance temperature of 307 °C a carbon powder. The density value of each carbon electrode for carbonization temperature of 650 °C, 700 °C, 750 °C and 800 °C is 0.557 g/cm3, 0.622 g/cm3, and 0.702 g/cm3, respectively. Microstructure analysis shows that amorphous structure for the activated carbon electrodesshowed by the presence of the peaks of 2θ around 24° and 44°.The results showed that the temperature of 700 °C is the best carbonization temperature in production of carbon electrodes from TKBA.